Tree—Open Grassland Structure and Composition Drive Greenhouse Gas Exchange in Holm Oak Meadows of the Iberian Peninsula - Mercedes Ibañez; María José Leiva; Cristina Chocarro; Salvador Aljazairi; Àngela Ribas; Maria-Teresa Sebastià (Agronomy, 2020)
Iberian holm oak meadows are savannah-like ecosystems that result from traditional silvo-pastoral practices. However, such traditional uses are declining, driving changes in the typical tree—open grassland structure of these systems. Yet, there are no studies integrating the whole ecosystem—including the arboreal and the herbaceous layer—as drivers of greenhouse gas (GHG: CO2, CH4 and N2O) dynamics. Here, we aimed at integrating the influence of tree canopies and interactions among plant functional types (PFT: grasses, forbs, and legumes) of the herbaceous layer as GHG exchange drivers. For that purpose, we performed chamber-based GHG surveys in plots dominated by representative canopy types of Iberian holm oak meadows, including Quercus species and Pinus pinea stands, the last a common tree plantation replacing traditional stands, and unraveled GHG drivers through a diversity-interaction model approach. Our results show the tree–open grassland structure, especially drove CO2 and N2O fluxes, with higher emissions under the canopy than in the open grassland. Emissions under P. pinea canopies are higher than those under Quercus species. In addition, the inclusion of diversity and compositional terms of the herbaceous layer improve the explained variability, with legumes enhancing CO2 uptake and N2O emissions. Changes in the tree cover and tree species composition, in combination with changes in the structure and composition of the herbaceous layer, will imply deep changes in the GHG exchange of Iberian holm oak meadows. These results may provide some guidelines to perform better management strategies of this vast but vulnerable ecosystem.